2015
DOI: 10.1117/1.nph.2.3.031208
|View full text |Cite
|
Sign up to set email alerts
|

All-optical bidirectional neural interfacing using hybrid multiphoton holographic optogenetic stimulation

Abstract: Our understanding of neural information processing could potentially be advanced by combining flexible three-dimensional (3-D) neuroimaging and stimulation. Recent developments in optogenetics suggest that neurophotonic approaches are in principle highly suited for noncontact stimulation of network activity patterns. In particular, two-photon holographic optical neural stimulation (2P-HONS) has emerged as a leading approach for multisite 3-D excitation, and combining it with temporal focusing (TF) further enab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 40 publications
0
24
0
Order By: Relevance
“…who focussed a single point onto a neuron to excite calcium activity in cell culture and hippocampal brain slices. Other researchers have found that, while two-photon single-point scanning can trigger an action potential in an opsin-expressing neuron2931, two-photon wide-field excitation is more effective at triggering the action potential5,3234. In a report using a similar laser configuration to our high-power femtosecond OPA system, a home-built three-stage OPA system was used to illuminate an entire fly brain, without spatial selectivity, to demonstrate that two-photon excitation of opsins is not limited to small numbers of neurons—potentially the entire brain of an animal can be exposed simultaneously35.…”
Section: Resultsmentioning
confidence: 99%
“…who focussed a single point onto a neuron to excite calcium activity in cell culture and hippocampal brain slices. Other researchers have found that, while two-photon single-point scanning can trigger an action potential in an opsin-expressing neuron2931, two-photon wide-field excitation is more effective at triggering the action potential5,3234. In a report using a similar laser configuration to our high-power femtosecond OPA system, a home-built three-stage OPA system was used to illuminate an entire fly brain, without spatial selectivity, to demonstrate that two-photon excitation of opsins is not limited to small numbers of neurons—potentially the entire brain of an animal can be exposed simultaneously35.…”
Section: Resultsmentioning
confidence: 99%
“…Such a task will additionally require the use of cell-type-specific fluorescent markers with spectral properties complementary to those of the genetically encoded sensors. Furthermore, the causality of one network with respect to the activity of another could be further explored by combining optical monitoring of one layer with electrical 63 and/or optogenetic stimulation 64 66 of the other layer.…”
Section: Discussionmentioning
confidence: 99%
“…We simultaneously performed 2P holographic optogenetic stimulation and 2P calcium imaging [12,19] in the olfactory bulb of awake, head-fixed mice outfitted with a cranial window. To boost excitation efficiency and temporal precision, our system used a low-repetition rate, amplified laser source (at 1028 nm) for stimulation [15,16,18,27], which was combined with a standard femtosecond oscillator at 920 nm for imaging ( Fig. 1A).…”
Section: All Optical Imaging and Photostimulationmentioning
confidence: 99%